Islam Syariat: Reproduksi Salafiyah Ideologis di Indonesia - Zain, Muhammad Fuad; Basit, Abdul (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2024)
Haedar Nashir's book on Islam Syariat: Reproduksi Salafiyah Ideologis di Indonesia is a fairly thick research comprising 604 pages. This book analyzes the Islamic movement that fights to implement Islamic Sharia in the context of state institutions carried out by MMI, HTI, and KPPSI. In this book, researchers combine literature and field research with emic data. The ideological thread of the Sharia Islamic Movement (Formalist) is a documentation of the